Draft Eighth Five Year Plan 1990-95 and Draft Annual Plan 1991-92 (Volume I and II) Statements Volume II - Planning Commission (Planning Commission, 1990)
Draft Eighth Five Year Plan 1990-95 and Annual Plan 1991-92 Statements Showing Employments (Major Head/Minor Head of Development-Wise) with the Correspondent Figure of Expenditure/Outlay Draft Eighth Five Year Plan 1990-95 and Annual Plan 1991-92 Statements Showing Employment (Scheme-Wise) with the Corresponding Figures of Expenditure/Outlay.
Draft Eighth Five Year Plan 1990-95 and Draft Annual Plan 1991-92